2020
DOI: 10.1016/j.fertnstert.2019.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting antimüllerian hormone levels for age and body mass index improves detection of polycystic ovary syndrome

Abstract: Objective: To examine whether accounting for a woman's age and body mass index (BMI) would improve the ability of antim€ ullerian hormone (AMH) to distinguish between women with (cases) and without (controls) polycystic ovarian syndrome (PCOS). Design: An opportunistic case-control dataset of reproductive age women having evaluations for PCOS as defined by National Institutes of Health criteria. Setting: Two medical centers in the United States enrolled women. Serum samples were analyzed for relevant analytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…BMI at age 18 has been shown to be a predictor of future ovulatory infertility [ 47 ]. Further, studies have demonstrated that BMI has an inverse association with AMH, making the findings we present here even more compelling [ 16 ]. Our findings are important as they offer the potential for building evidence-based tools tailored to help empower at-risk population for improved fertility outcomes.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…BMI at age 18 has been shown to be a predictor of future ovulatory infertility [ 47 ]. Further, studies have demonstrated that BMI has an inverse association with AMH, making the findings we present here even more compelling [ 16 ]. Our findings are important as they offer the potential for building evidence-based tools tailored to help empower at-risk population for improved fertility outcomes.…”
Section: Discussionsupporting
confidence: 60%
“…To assess the association between markers of ovarian reserve and each dietary pattern, multivariate linear regression was then performed controlling for age, BMI, smoking status, and physical activity. Subjects were stratified by BMI < 25 kg/m 2 and BMI ≥ 25 kg/m 2 as BMI is known to be associated with markers of ovarian reserve [ 16 ]. KPAS and the dietary pattern scores were divided into quartiles, with the lowest quartile representing women least adherent to the behavior.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are similar to those of previous studies, which demonstrated that AMH was correlated with PCOS severity [24][25][26] or AMH was a strong predictor for amenorrhea in PCOS. 26 Also, it has recently been reported that AMH is a valuable marker for the diagnosis of PCOS in numerous studies, [27][28][29][30][31][32][33] although the cutoff value has not yet been determined.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its low cost and independency of operator ultrasound skills, AMH has been well established to be a signi cant correlator and a biologic marker for the antral follicle counts (AFC), thus re ecting the ovarian reserve in the female population. Therefore, it can potentially replace the ultrasound in the detection of PCOM and hence it may play a role in the diagnosis of PCOS [32]. Moreover, these bene ts may be particularly useful in the adolescent and reproductive age population and in certain cultures since evaluation of the ovaries by transvaginal ultrasonography may not be considered or even possible due to virginal status.…”
Section: Amh Role In the Detection Of Pcom And Pcosmentioning
confidence: 99%